The Influence of Literature on Lana’s Character Development in The Novel The Day I Fell Into A Fairytale - Adiyatma, Savira Fitri (Prosodi Jurnal Ilmu Bahasa dan Sastra, 2023)
This study aims to reveal Lana's character development in the novel The Day I Fell into a Fairytale written by Ben Miller. To reveal the objective, this study is using new criticism theory based on direct and indirect characterization that is depicted in the story. Besides, close reading is utilized in the process of analysis, thus descriptive-qualitative strategy will be applied in this study. The data in this study were taken from the novel, mainly gathered from words, phrases, sentences, and symbolism. Furthermore, the writer found that Lana’s character development is highly influenced by her experience jumping into Grimm’s Fairytale world which symbolized her action reading Grimm’s fairytale.